PREDICTORS OF INFORMATION AND COMMUNICATION TECHNOLOGY USAGE AMONG SCIENCE TEACHERS IN FEDERAL UNITY SCHOOLS IN NIGERIA (2014)
Information and Communication Technology (ICT) has great potential in transforming the traditional and teacher-centred mode of science teaching in schools into a modern and rich student-centred mode; hence, the encouragement of its usage in unity schools across Nigeria. Regardless of its encouragement and adoption in unity schools, the level of its usage among science teachers is still relatively low with negative consequences on the teaching and learning of science subjects. Previous studies on factors attributable to such low usage among science teachers have concentrated more on the relative influence of the predicting factors than their combined effects. This study, therefore, examined the extent to which demographic factors (age, gender, subjects‟ taught, educational qualification, teaching experience and ICT use-experience), computer self-efficacy (CSE), attitude towards ICT, ICT access and existence of school library media centre (SLMC) predicted ICT usage among science teachers in federal unity schools (FUSs) in Nigeria. The study adopted the correlational research design. The multistage sampling procedure was adopted to select 464 science teachers and 25 school library media specialists from 25 selected FUSs in Nigeria. Six instruments were used: ICT Availability Scale (r=0.72), ICT Access Scale (r=0.83), Computer Self-Efficacy Scale (r=0.85), ICT Attitude Scale (r=0.65), ICT Usage Scale (r=0.89) and Role of SLMC Scale (0.75). These were complemented with an observation checklist. Ten research questions were answered and four hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson‟s product moment correlation and multiple regression. Demographic variables, CSE, attitude towards ICT, ICT access and existence of SLMC significantly predicted ICT usage (F (10, 342) = 21.17) and jointly accounted for 36.4% in the total variance of the dependent measure. Their relative contribution were: attitude towards ICT (β= .343, t=4.83), teaching experience (β=-.334, t=5.189), educational qualification, (β=-.275, t=5.26), computer self efficacy, (β=.165, t=2.34) ICT use- experience (β=.130,t=2.53). Observed relationships among the demographic variables and ICT usage were: age (r = -.301), gender (r = -.033), subjects taught (r = -.162), educational qualification (r = -.110), teaching experience (r = -.277) and ICT use- experience (r = .188). ICT usage was significantly positively related with CSE (r = .328), attitude towards ICT (r = .470), ICT access (r = .457) and existence of SLMC (r = .231). Demographic variables, CSE, attitude towards ICT, ICT access, ICT use-experience and existence of SLMC slightly predicted ICT usage among science teachers in federal unity schools in Nigeria. To ensure high level of ICT usage by science teachers and improve the teaching and learning of science subjects in federal unity schools in Nigeria, adequate attention should be given to science teachers‟ demographic variables and other factors considered in the study. In addition, SLMC should be adequately equipped so as to function effectively in providing support for efficient ICT usage by science teachers in Nigeria. Key words: ICT usage and access, Science teachers in Nigerian federal unity schools, School library media centre. Word count: 478